ANALISIS RASIO EFEKTIVITAS ALOKASI DANA DESA PADA DESA PASIR PUTIH KABUPATEN KONAWE KEPULAUAN (STIE ENAM ENAM KENDARI, 2022)
This study aims to determine the Effectiveness Ratio Analysis of Village Fund Allocation in Pasir Putih Village, West Wawonii District, Konawe Islands Regency. The research method used is descriptive quantitative. The data processed is in the form of the Village Fund Allocation of Pasir Putih Subdistrict, West Wawonii District, Konawe Islands Regency for the last 3 (three) years. The selection of descriptive quantitative in this study is based onresearch that wants to analyze financial performance using effectiveness ratios. The results of the research and discussion show that the Effectiveness Ratio of Village Fund Allocations in Pasir Putih Village, West Wawonii District, Konawe Islands Regency from 2018-2020 is in the effective category, because the level of effectiveness is at 90-100%. The level of effectiveness of each year, in 2018 it reached 98%, in 2019 it reached 98%, and in 2020 it reached 100%. The effectiveness of the Village Fund Allocation in Pasir Putih Village is included in the very effective category according to the level of community needs, right on target and effective. This is in accordance with the provisions of the Ministry of Home Affairs, Ministry of Home Affairs Number 690,900,327.